The Influence of Visionary Leadership and Quantum Leadership on the Improvement of Learning Quality in Senior High Schools in South Aceh Regency - Nita, Santi; Usman, Nasir; Khairuddin, Khairuddin; Niswanto, Niswanto (Formosa Journal of Applied Sciences, 2025)
Ideally, a principal combines these styles: visionary leadership provides a clear direction for the school, while quantum leadership fosters a conducive environment to achieve that vision. This study aims to analyze the impact of visionary and quantum leadership on improving learning quality. Using a quantitative approach, the study involved 58 teachers and 4 principals from four high schools: SMA Negeri 1 Tapaktuan, SMA Negeri 3 Kluet Utara, SMA Negeri 1 Bakongan, and SMA Negeri 1 Kluet Utara. Data was collected through observation, questionnaires, and documentation. Data analysis utilized simple and multiple linear regression tests. The results show that both visionary and quantum leadership have a significant positive effect on learning quality improvement. This study concludes that combining these leadership styles optimally enhances the quality of the learning process.